2008
DOI: 10.1007/s00216-008-1911-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave biosensors: a review

Abstract: This review presents an overview of 20 years of worldwide development in the field of biosensors based on special types of surface acoustic wave (SAW) devices that permit the highly sensitive detection of biorelevant molecules in liquid media (such as water or aqueous buffer solutions). 1987 saw the first approaches, which used either horizontally polarized shear waves (HPSW) in a delay line configuration on lithium tantalate (LiTaO(3)) substrates or SAW resonator structures on quartz or LiTaO(3) with periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
391
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(404 citation statements)
references
References 87 publications
0
391
0
Order By: Relevance
“…Before, only non-leaky Lamb wave (Lohr and Rose, 2003) on non-piezoelectric substrates or shear horizontal waves on piezoelectric substrates (Balantine et al, 1997;Thomson and Stone, 1997) were investigated, because it was thought that bulk acoustic waves or surface acoustic waves with a dominant vertical displacement would be inapplicable for coating detection in a liquid environment (Länge et al, 2008;Calabrese et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Before, only non-leaky Lamb wave (Lohr and Rose, 2003) on non-piezoelectric substrates or shear horizontal waves on piezoelectric substrates (Balantine et al, 1997;Thomson and Stone, 1997) were investigated, because it was thought that bulk acoustic waves or surface acoustic waves with a dominant vertical displacement would be inapplicable for coating detection in a liquid environment (Länge et al, 2008;Calabrese et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the technological applications of this well-suited material include: bulk acoustic wave devices, acoustic transducers, piezoelectric transducers and piezoelectric sensors [28]. Its good mechanical stability and chemical stability make LTA already widely used as a substrate in surface acoustic wave (SAW) devices [29]. LiTaO 3 has twelve independent acoustic physical constants.…”
Section: Model and The Calculation Methodsmentioning
confidence: 99%
“…SAW signal generating and receiving elements, called interdigital transducers (IDTs), are realized by interdigitated microelectrodes. This standard electrode configuration has been successfully optimized towards high-sensitive SAW sensors and is highly sensitive to a number of physical parameters, e.g., humidity, temperature, and mass [1]. It has been recently shown that the conventional 2-port transmission approach can be significantly simplified by utilizing only one single IDT for SAW generation and simultaneously as sensing element.…”
Section: Introductionmentioning
confidence: 99%